MOON-test – Determination of Motor Performance in the Pediatric Oncology - Götte, M.; Kesting, S.; Albrecht, C.; Worth, A.; Bös, K.; Boos, J. (Klinische Pädiatrie, 2013)
Pediatric cancer patients suffer from various negative consequences due to the disease, the medical therapy and the inactivity during the intensive treatment. Only few studies have systematically identified the adverse effects of cancer on motor performance in childhood.To determine the motor performance of pediatric cancer patients, a motor performance test was developed which is applicable for this specific patient group. Eight test items with reference values for healthy children were merged to the MOON-test (test for motor performance in the oncology).MOON was tested for feasibility and acceptance in 33 patients aged 4–18 years. Feasibility was confirmed for children with different types of cancer (hematological malignancies and solid tumors) and with amputation, endoprosthesis, during aplasia as well as reduced general condition. Furthermore the patients showed a broad acceptance.Based on the study findings, the use of MOON-test as a standardized motor performance diagnostic tool in clinical routine of oncological acute clinics as well as rehabilitation clinics can be recommended.·
Keywords: pediatric cancer patients; pediatric oncology; motor abilities; motor performance diagnostic tool; physical activity; MOON